Analysis on the Relationship Between the Profit Tax and Investments in the Context of a Globalised World. Case Study – Romania - Dumitru Cristian Oanea; Marius Constantin Apostoaie (CES Working Papers, 2010)
Although it is a relative old concept, having ruts in the writings of the late ,,60s, globalization has become in current times a cliché, being used in many parts of the world and in many languages but not having a specific definition. Financial globalization is considered to be the core element of the process of globalization and consists in a complex integration of financial markets through exchange and financial flows. In this context, the economic agents are considered to be important players, given the fact that fortheir investments they appeal to financial recourses wherever they may be. However there investment behavior is greatly influenced by the state, through the fiscal policy, especially through a very important instrument at its disposal, the profit tax rate.The aim of this paper is to emphasize the evolution of the relationship between the profit tax and investments, in the case of Romania from 1990 until 2008, trying to show particular developments of each of this two variables studied and the relations between them, the amplitude of influence exercised by them. The paper also focuses upon a better understanding of how the variables analyzed influence the real economy in this globalized environment.
Keywords: 330; globalization; economic policy; investment; profit tax rate; FDI